Study on Electrical and Physical Properties of Lithium Cobalt Oxide Thin Films for Renewable Energy Application - Syed Ahmad Tarmizi, Syarifah Aqilah; Nayan, Nafarizal (Evolution in Electrical and Electronic Engineering, 2025)
The work described in this paper seeks to understand the impact of post-deposition treatments on the electrical, mechanical and physical properties of lithium cobalt oxide (LiCoO2) thin films in order to improve their applicability as cathode materials in lithium-ion batteries. The thin films of LiCoO2 were deposited on nickel substrates by RF magnetron sputtering at room temperature, and then thermal annealed at 200 °C temperature during 1 hour and reactive ion etching (RIE) at 100 W RF power, 20 sccm Ar flow, 100 mTorr working pressure, for the duration of 2 minutes. The characterization of surfaces by FESEM and AFM showed that annealing boosted the average grain size (34.2nm untreated to 39.0nm) and roughness (Ra 5.2nm to 7.4nm) and etching further promoted grain size to 42.3nm and roughness to 9.8nm. Local conductivity was found to increase sixfold as measured by conductive AFM, 0.3 nA (bare) to 1.9 nA (etched). Contact angle measurements showed an increase in wettability after annealing ( 25) and a decrease in wettability after etching ( 50). The combination of these morphological and electrical improvements leads to an increase in the electrochemically active surface area, optimization of lithium-ion transport pathways, and a decrease in interfacial resistance - leading to improved charge storage and cycling stability. These results indicate the performance of LiCoO2 thin films can be greatly enhanced by adjusting the surface structure by controlled annealing and etching to meet the requirements of advanced energy storage devices.